Bifunctional cationic solid lipid nanoparticles of β-NaYF4:Yb, Er upconversion nanoparticles coated with a lipid for bioimaging and gene delivery. Issue 43 (17th May 2017) - Song, Chenxi; Zhang, Shubiao; Zhou, Quan; Shi, Lei; Du, Linying; Zhi, Defu; Zhao, Yinan; Zhen, Yuhong; Zhao, Defeng
Abstract : We demonstrate the possibility of novel bifunctional cationic solid lipid nanoparticles (CSLNs) for bioimaging and gene delivery through peptide lipid coated UCNPs. Abstract : β-NaYF4 :Yb, Er upconversion nanoparticles (UCNPs) were synthesized by a one-pot solvothermal method. The UCNPs were characterized through X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) to prove that they possessed hexagonal crystal phase with uniform particle size distribution. The cationic solid lipid nanoparticles (CSLNs) were then obtained by coating the UCNPs with a lipid. Further analysis by FTIR, XRD and TEM indicated the lipid can successfully coat UCNPs, and the coating process had no obvious influences on morphology and crystallization of the UCNPs. Furthermore, the CSLNs were used for bioimaging in cells and delivering small interfering RNA (siRNA). Cellular bioimaging and upconversion luminescence studies clearly demonstrated that the CSLNs could effectively enter into cells with the help of the lipid. Silencing assays and cytotoxicity in A549 cells convincingly showed that the CSLNs could effectively deliver siRNA and possessed low cytotoxicity and good biocompatibility. Thus, the bifunctional CSLNs could be used as a potential candidate in bioimaging and therapeutic applications.